High-Throughput Screens for eEF-2 Kinase. (March 2014) - Devkota, Ashwini K.; Warthaka, Mangalika; Edupuganti, Ramakrishna; Tavares, Clint D. J.; Johnson, William H.; Ozpolat, Bulent; Cho, Eun Jeong; Dalby, Kevin N.
EEF-2 kinase is a potential therapeutic target for breast cancer, gliomas, and depression. No potent inhibitors of eEF-2K have been reported, and thus development of high-throughput assay systems may expedite the process. Two high-throughput assays are described for eEF-2K using recombinant, tag-free enzyme purified from bacteria. The first is a fluorescence-based assay that uses the phosphorylation of a Sox-based peptide substrate by eEF-2K, which results in a 5-fold increase in fluorescence emission, allowing for continuous monitoring of the kinase activity. The second is a luminescence-based assay that produces a luminescence signal, which correlates with the amount of adenosine triphosphate remaining in the kinase reaction. Both assays have been optimized and miniaturized for a 384-well plate format and validated in screens. In conclusion, we demonstrated that a traditional radiolabeled assay can be readily transferred to universal spectroscopic assays that are robust and will facilitate high-throughput screening of larger size libraries for the identification of small-molecule inhibitors and significantly contribute to the development of therapies for targeting eEF2K.